Globalization and reproductive tourism in the United Arab Emirates - Inhorn, Marcia C; Shrivastav, Pankaj (Asia-Pacific journal of public health, 2010)
Over the past 2 decades, the discipline of anthropology has been deeply concerned with the processes and effects of globalization around the world. One of the major anthropological theorists of globalization, Arjun Appadurai, has delineated a "global cultural economy" in which global movements operate through 5 pathways, which he famously called "scapes." This article uses the language of "scapes" to examine the global flows involved in so-called "reproductive tourism," or the search for assisted reproductive technologies across national and international borders. Reproductive tourism entails a complex "reproscape" of moving people, technologies, finance, media, ideas, and gametes, pursued by infertile couples in their "quests for conception." This article examines reproductive tourism to and from the United Arab Emirates, which is now the site of intense globalization and global flows, including individual and population movements for the purposes of reproductive and other forms of medical care.